2021
DOI: 10.1186/s13148-021-01086-6
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss after Roux-En-Y gastric bypass surgery reveals skeletal muscle DNA methylation changes

Abstract: Background The mechanisms of weight loss and metabolic improvements following bariatric surgery in skeletal muscle are not well known; however, epigenetic modifications are likely to contribute. The aim of our study was to investigate skeletal muscle DNA methylation after weight loss induced by Roux-en-Y gastric bypass (RYGB) surgery. Muscle biopsies were obtained basally from seven insulin-resistant obese (BMI > 40 kg/m2) female subjects (45.1 ± 3.6 years) pre- and 3-month post-surgery with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…We hypothesized that averaged global methylation pre- versus post-training would be unchanged following the training. We [ 19 ] and others [ 20 ] have performed methylation studies with and without various interventions and showed minimal to no changes at the global level. We showed a similar finding here in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesized that averaged global methylation pre- versus post-training would be unchanged following the training. We [ 19 ] and others [ 20 ] have performed methylation studies with and without various interventions and showed minimal to no changes at the global level. We showed a similar finding here in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Participants reported fasting to either the CSIU or CATS to undergo an 80 mU/m 2 euglycemic hyperinsulinemic clamp with muscle biopsy, as previously described [ 19 , 39 ]. Briefly, a primed infusion of 6,6 di-deuterated glucose was started at −120 min to determine the basal rate of glucose metabolism.…”
Section: Methodsmentioning
confidence: 99%
“…Some authors have also observed lower overall methylation levels after RYGB in subcutaneous adipose tissue (SAT) [ 16 , 17 ]. Conversely, more recent studies have observed higher methylation levels at cytosine-phosphate-guanine dinucleotides, or CpG sites, after RYGB and SG procedures in peripheral blood [ 15 ], as well as higher global methylation levels in skeletal muscle after RYGB [ 18 ]. These discrepancies may partly be explained by tissue-specific DNA methylation [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was observed a DNA methylation remodeling in adipose tissue after 6 months postoperative, in accordance with previous reports of changes in blood, liver, muscle, and adipose tissue. [ 14–17 ] It has been shown that the methylation profiles of subcutaneous adipose tissue have a high correlation with visceral adipose tissue, so this tissue could be a good mirror of what occurs in other fat deposits. [ 12 ]…”
Section: Discussionmentioning
confidence: 99%